How to combine the entry of young people in the labour market with the retention of older workers? - Werner Eichhorst; Tito Boeri; An DE Coen; Vincenzo Galasso; Michael Kendzia; Nadia Steiber (IZA Journal of European Labor Studies, 2014)
This paper provides an overview of the employment situation of young and old workers in the EU Member States, setting out the most recent development during the crisis and dealing with policies implemented to promote the employment of both groups. The evidence collected shows that there is no competition between young and older workers on the labour market. Structural or general policies to enhance the functioning of EU labour markets are crucial to improving the situation of both groups. However, the responsibility for employment policies still predominantly lies within Member States of the European Union, although initiatives taken at the EU level can provide added value, particularly through stimulating the exchange of experiences and facilitating regional and cross-border mobility throughout the EU.
Keywords: 330